KAJIAN METODE MUBADALAH: DEFINISI, LANDASAN TRADISIONAL, DAN PENERAPAN TAFSIR - Diah Ramadhani; Khairil Alwi (Cahaya Ilmu Bangsa Institute, 2025)
The Mubadalah method is an approach to Islamic interpretation and thought that emphasizes the principles of reciprocity and justice between men and women. This approach emerged as a critique of religious interpretations that tend to be gender-biased within classical Islamic traditions. By positioning men and women as equal subjects, the method promotes a fair, non-discriminatory, and contextual reading of the Qur’an and Hadith. This study uses a qualitative method through literature review to explore the basic concepts, main principles, and practical applications of Mubadalah in gender-related issues such as marital relationships, women's leadership, and social rights. The findings show that the Mubadalah method offers an alternative interpretation that upholds justice and aligns with the values of rahmatan lil ‘alamin. Therefore, this approach contributes significantly to the development of Islamic thought that is more inclusive, relevant, and responsive to contemporary social challenges.